Poly Methyl Methacrylate Denture Base Filled With Nitrile Butadiene Rubber And Ceramic Particles - Alhareb, Ahmed Omran Salem (2017)
Poly (methyl methacrylate) (PMMA) resin is the most common and suitable material for fabrication of denture base application. However, PMMA denture base material is poor in impact strength (IS) and fracture toughness (KIC) due to its brittleness. In this study, the properties of PMMA denture base composite was enhanced by incorporation of ceramic fillers (Al2O3 and yttrium stabilized zirconia (YSZ) powders) as toughening particles together with nitrile butadiene rubber (NBR) particles as impact modifier. The PMMA powder was mixed with liquid monomer and stabilized with 0.0025% hydroquinone. Benzoyl peroxide (BPO) and ethylene glycol dimethacrylate (EGDMA) were used as initiator and cross-linking agent, respectively. This study was divided into four different stages. The first stage, different ratios of NBR particles (5, 7.5 and 10 wt.%) was mixed with ceramic fillers fixed at 5 wt..% (Al2O3 and YSZ). In this stage, the effects of both untreated and treated ceramic fillers by silane (γ-MPS) were determined through their impact strength (IS), fracture toughness (KIC) and microstructure morphology examination. It was found that the optimum ratio was 7.5 wt.% of NBR particles when ceramic fillers fixed at 5 wt.% (for both untreated and treated by silane). In the second stage, the optimum ratio of ceramic fillers (Al2O3 and YSZ fillers) (fixed at 5 wt.%) together with 7.5 wt.% NBR (optimum ratio obtained from first stage) was investigated. The optimum ratio of second stage was 2.5 wt.% Al2O3 and 2.5 wt.% YSZ as mixtures particles. Third stage was used to study the effect of filler loading in the PMMA matrix. It is noticed that for 1 to 5 wt.% of filler loading, the IS and KIC values were increased compared to PMMA matrix and commercial PMMA. Final stage, the optimum ratio of filler loading (5 wt.%) was evaluated for both surface roughness (Ra) and residual MMA monomer. The result of Ra of reinforced PMMA denture base by the conventional laboratory polishing system (lathe polishing) showed smoother surfaces compared to threshold level (0.2 μm) from 2.11 μm to 0.19 μm. While the amount of residual MMA monomer of reinforced PMMA denture base (1.016%) was reduced when compared to commercial PMMA (1.916%) and PMMA matrix (1.080%).